An integrated OEE framework for structured productivity improvement in a semiconductor manufacturing facility. Issue 5 (6th March 2020) - Cheah, Chew Keat; Prakash, Joshua; Ong, Kok Seng
Abstract : Purpose: The purpose of this paper is to introduce a practical integrated overall equipment effectiveness (OEE) framework that encompasses the core characteristics of OEE. Design/methodology/approach: The paper reviewed the backgrounds of OEE and improvement frameworks and explored the limitations. An integrated OEE framework was developed by synergizing the strengths of OEE and improvement frameworks to complement the shortcomings. This new framework underlies the OEE concepts and provides structural improvement steps. It was applied to systematically assist and guide OEE practitioners in a case study. Findings: The review of OEE literature found that there is a lack of improvement frameworks with systematic steps specifically developed for OEE implementation. Conversely, a review on improvement frameworks of different methodologies revealed that they do not fully capitalize on the use of performance measures as benchmarks and improvement drivers. An integrated framework that incorporated the advantages of both OEE and conventional improvement frameworks was developed and validated through a case study over a period of 38 weeks. The OEE performance before the improvements was low (73.4 percent) due to high availability losses (76.5 percent). Both OEE and availability achieved the target of 76.5 percent and 80 percent, respectively, after using the framework for improvements. Research limitations/implications: The reviewed papers represent a sample of papers present in the literature and were selected based on relevancy. A greater number of papers incorporated into the literature review would certainly bring out a more comprehensive study. Practical implications: The proposed integrated OEE framework provides OEE practitioners with systematic directions and steps combined with benchmarking and loss prioritization features for effective improvement efforts. In addition, it provides overview for the practitioners to make better decisions in project management. This helps address the common issues of practitioners not sure of what the next improvement step is. A case study using the proposed framework at a semiconductor company had successfully achieved the OEE benchmarks and set target for conversion time. Originality/value: This paper provides a new integrated OEE framework offering a systematic approach toward implementing OEE improvements.